Peningkatan Pengetahuan Membuat Digital Asset dan Komersialisasinya Pada Siswa SMK Kesehatan Aras Depok - Rofi'i, Muhammad; Hagabean, Ananta; Gani, Ariel Nian; Faisal, Muhammad; Tulasmiyanti, Novia; Rahmasuciana, Dioni Yurinda (LPPM Universitas Bina Sarana Informatika, 2024)
There are two primary challenges faced by students of SMK Kesehatan Aras Sawangan Depok. Firstly, there is a proficiency issue in videography and photography, considering SMK Kesehatan Aras specializes in health education and lacks focus on videography, photography, or visual communication design. Secondly, students encounter difficulties in utilizing digital platforms as avenues for selling digital assets such as videos and photos. Addressing these issues is crucial for enabling students to commence monetizing digital assets online. The objective of this training program is to enhance students' knowledge and skills in producing digital assets and commercializing them through the Gettyimages application. The method employed is Asset Based Community Development (ABCD). This community service activity was attended by 27 Aras Vocational School students. Based on pretest and posttest analysis, it shows that the increase in participants' knowledge varied between 82%-100%, with an average increase in understanding for the 27 participants of 91.92%. So it can be concluded that the objectives of this training have been achieved, this training has had a positive impact as shown by the increase in participants' understanding of 11 aspects of the science of selling digital assets in the form of videos and photos on the Gettyimages platform.